Investigating the Effectiveness of Financial Management in Local Authorities’ Performance: case of Chirumanzu RDC - Chekeche, Raphael (Midlands State University, 2017)
The research was carried out to analyze the effectiveness of financial management in the performance of Chirumanzu Rural District Council. An investigation was incorporated as to whether the council has sufficient funds to finance its operations and also whether the council has been implementing effective financial management approaches. The research made use of related literature so as to strengthen and support the research aspects. Reliable and valid data was gathered through questionnaires and interviews at Chirumanzu Rural District Council. A sample size of 17 members which consisted of the council treasurer and finance department staff, the CEO and administration staff, the council chairperson and the finance committee was consulted to respond to the questionnaires and interviews. The analysis of the gathered data was done through tables, graphs, pie charts and descriptive summaries. Conclusions revealed that the council’s financial management system was ineffective since the council was failing to procure adequate funds, manage available funds and provide sufficient public services. The major areas of default were identified which include inadequate financial monitoring and poor financial decision making. The research then made recommendations that the council should restructure its financial budget as a financial management tool and reinforce its financial control systems.